HUBUNGAN PENGETAHUAN IBU TENTANG ASI DENGAN STATUS GIZI PADA BALITA USIA 1 SAMPAI 2 TAHUN DI DESA PLAMPANGREJO BANYUWANGI - Viona Rindu Pristia; Sukma Sahadewa; Maria Juliati Kusumaningtyas; Masfufatun (Calvaria Medical Journal, 2025)
Background: Malnutrition in children is a serious issue that can be prevented through optimal nutritional fulfillment. Breastfeeding practices and maternal knowledge are key determinant factors during the golden period of growth. Objective: This study aims to analyze the relationship between maternal knowledge regarding breastfeeding and the nutritional status of toddlers aged 1 to 2 years in Plampangrejo Village, Banyuwangi. Method: This research employed a quantitative approach with an analytical observational design using a cross-sectional study. The study population consisted of mothers with children aged 1 to 2 years residing in Plampangrejo Village. Data were analyzed using the Chi-square statistical test. Results: The findings indicate a significant and strong correlation between maternal knowledge of breastfeeding and the nutritional health of infants aged 1 to 2 years in Plampangrejo Village, Banyuwangi. This is evidenced by a p-value of 0.000, which is less than the significance level (α = 0.05).Conclusion: There is a significant relationship between maternal knowledge about breastfeeding and the nutritional status of toddlers. Higher maternal understanding of breastfeeding correlates with better nutritional outcomes for children aged 1 to 2 years.